Multi-production of freshwater, hydrogen, and cooling through waste heat recovery of a gas turbine-modular helium reactor: Exergy-economic assessment and optimization - Badreddine Ayadi; Ali Basem; Loghman Mostafa; Aman Sharma; Aashim Dhawan; Prabhat Sharma; Aboulbaba Eladeb; Lioua Kolsi (Case Studies in Thermal Engineering, 2025)
The present study discloses that the waste heat of a gas turbine-modular helium reactor (GT-MHR) can be recuperated to device a polygeneration system utilizing two organic Rankine cycles (ORCs) and four thermoelectric generators (TEGs). Two TEGs are used in the layout to recuperate the energy loss of the helium flow before entering the compressors of the GT-MHR, while two other TEGs are utilized instead of the condensers of the ORC 1 and ORC 2. The favorable output power is generated in the turbine of the GT-MHR system, and the total power generated by TEG 1 and TEG 2 is considered the input electricity of a proton exchange membrane electrolyzer (PEME) to generate hydrogen. The power generated by ORC 1 and ORC 2 is utilized to produce sub-zero cooling and potable water by a transcritical CO2 refrigeration system (TCRS) and a reverse osmosis desalination unit (RODU), respectively. The thermo-economic optimization of the setup reveals a payback period of 1.42 years, exergy efficiency (ηex) of 46.44 %, and output electricity of 27.36 MW for the system. The utilized subsystems integrated with the GT-MHR contribute to 10 % of the overall investment cost rate (Z˙tot) of the configuration. However, 496 kW of the input exergy is recovered through the production of cooling, freshwater, and hydrogen with rates of 2.57 MW, 40.4 kgs−1, and 3.88 kgh−1, respectively. The total cost rate (C˙tot) and the specific cost of polygeneration (cpoly) were obtained as 1247 $h−1 and 9.54 $GJ−1, respectively. A comparison of the system performance and previous polygeneration configurations based on a gas turbine revealed the superiority of the present layout in terms of ηex.